Palladium‐Catalyzed Ligand‐Controlled Selective Synthesis of Aldehydes and Acids from Aryl Halides and Formic Acid. Issue 16 (27th June 2017) - Wu, Fu‐Peng; Peng, Jin‐Bao; Meng, Ling‐Shen; Qi, Xinxin; Wu, Xiao‐Feng
Abstract: Selective synthesis is in the core of modern organic chemistry. In this communication, a novel ligand‐dependent palladium‐catalyzed carbonylation procedure for the divergent synthesis of aldehydes and carboxylic acids from easily available aryl halides was established. Under the same reaction conditions, the reaction pathway could be controlled by the ligands applied to give formylated and carboxylated products selectively. Sterically hindered monodentate ligands facilitated the reductive carbonylation and provided aldehydes, whereas bidentate ligands preferred the carboxylation reaction and produced carboxylic acids. A wide range of functional groups were tolerated, and the products were, in general, obtained in moderate to excellent yields. Abstract : Take your pick : A method for the ligand‐controlled divergent synthesis of aldehydes and carboxylic acids from aryl halides under identical reaction conditions is established. Generally, small sterically hindered monodentate alkylphosphines facilitate the formation of aldehydes, whereas wide‐bite‐angle bidentate ligands promote the formation of acids. Cy=cyclohexyl, DCC=dicyclohexylcarbodiimide, Xantphos=4, 5‐bis(diphenylphosphino)‐9, 9‐dimethylxanthene.